If <em>f(x)</em> = 1/<em>x</em> - 2, then the average rate of change between <em>x</em> = 4 and <em>x</em> = 8 is
(<em>f</em> (8) - <em>f</em> (4)) / (8 - 4) = ((1/8 - 2) - (1/4 - 2)) / 4 = -1/16
If you meant <em>f(x)</em> = 1/(<em>x</em> - 2), then it would be
(<em>f</em> (8) - <em>f</em> (4)) / (8 - 4) = (1/(8 - 2) - 1/(4 - 2)) / 4 = (1/6 - 1/2) / 4 = -1/12
<em>Make sure to check which one is the correct function!</em>
The option D) x + x+2 + x+4 = 53 represents the exact equation of sum of three consecutive odd integers which is equal to 53.
<u>Step-by-step explanation:</u>
The sum of the three consecutive odd integers = 53
<u>To frame the equation :</u>
- Let us consider any of the three consecutive odd integers.
- Let us take 1,3,5 as the three consecutive odd integers.
Assume the first odd integer as 'x'. In this case, (x=1)
- The second consecutive odd integer is 3.
- The difference between 1 and 3 is 2.
Therefore, the second consecutive odd integer is x+2.
- The third consecutive odd integer is 5.
- The difference between 1 and 5 is 4.
Therefore, the third consecutive odd integer is x+4.
This means that, the sum of any three consecutive odd integers are given as x + x+2 + x+4.
Given that,
Sum of the three consecutive odd integers is 53.
The first odd integer + second odd integer + third odd integer = 53
x + x+2 + x+4 = 53.
The option D) x + x+2 + x+4 = 53 represents the exact equation of sum of three consecutive odd integers which is equal to 53.
Answer:
y-10=2/3(x-8)
Step-by-step explanation:
(y2-y1)/(x2-x1) is the equation for slope so put your points in you get 2/3 once simplified then its just a matter of putting points in the equation y-y1= m(x-x1)
We are given:

Our goal in solving for any variable, in this case is x, we need to isolate x on one side of the variable. Let's start by subtracting 7x from both sides, which will cancel the +7x on the right side. We are then left with:

Now, we want to move that +10 to the other side so our x is all by itself. Let's subtract 10 from both sides, which will cancel the +10 on the right leaving us with:

Since we cannot have a coefficient when solving for x, we need to divide both sides by -3.

When we divide, our answer is:

Answer:
1st box: Asso. prop= m+(4+x)
2nd box: Comm. Prop= m+4=4+m
3rd box: iden. prop= m+0=m
4th box: Zero prop: m x 0=0